Spatial and functional changes in built-up areas in selected slovene rural settlements after 1991 - Topole, Maja; Bole, David; Petek, Franci; Repolusk, Peter (Acta geographica Slovenica, 2006)
We determined changes in the settled areas of rural settlements by means of aerial photos and orthophotos, statistical data, and data obtained through field research. The expert sample comprised 14 rural settlements with 500 to 1100 inhabitants from a variety of Slovene natural and statistical regions which in the past ten-year period have shown positive growth in the number of inhabitants, jobs, and houses. We identified how the following categories changed in settled areas in the period from 1991 to 2005: residential areas, areas with central functions (supply, service, and business), traffic areas and green and other open spaces. Most apparent were differences among the types of settlements. We related land use to the relief and type of settlement, to the geographical location of the settlement, to changes in its structure, and to trends in the number of jobs and extent of commuting.